2018
DOI: 10.1097/qad.0000000000001918
|View full text |Cite
|
Sign up to set email alerts
|

Preferences for linkage to HIV care services following a reactive self-test

Abstract: Populations in Malawi and in Zambia were responsive to low-cost, HIV care services with short waiting time provided either at the community or privately at health facilities. Hard-to-reach groups could be encouraged to link to care with targeted support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 33 publications
1
28
0
Order By: Relevance
“…The agenda, which was in part funded by other partners, included formative research and accuracy studies to establish that HIVST was acceptable, safe, and could be correctly performed by priority populations . Further studies tested user preferences and established simple distribution models aimed at using HIVST for maximum public health impact . Data from these early distribution models informed costing and cost‐effectiveness studies to establish the evidence for HIVST scalability and sustainability .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The agenda, which was in part funded by other partners, included formative research and accuracy studies to establish that HIVST was acceptable, safe, and could be correctly performed by priority populations . Further studies tested user preferences and established simple distribution models aimed at using HIVST for maximum public health impact . Data from these early distribution models informed costing and cost‐effectiveness studies to establish the evidence for HIVST scalability and sustainability .…”
Section: Discussionmentioning
confidence: 99%
“…Further studies tested user preferences and established simple distribution models aimed at using HIVST for maximum public health impact . Data from these early distribution models informed costing and cost‐effectiveness studies to establish the evidence for HIVST scalability and sustainability . This collaboration helped generate important aspects of the evidence needed to inform WHO Guidelines on HIVST and Partner Notification (i.e., HIVST normative guidelines) published in December 2016, and the operational guidance at country level that followed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…one-third of men less than 30 years old reported that they were unmarried. These findings highlight the crucial need to better understand the behaviors and preferences of men living with HIV [45][46][47][48], in order to identify improved and specific engagement and retention strategies-especially among those who are young and may lack social or partner support, as such individuals traditionally have poor engagement throughout the HIV care continuum [49,50]. While optimum strategies are not well known, these may include improved access to self-testing [51], use of incentives [8], and male-friendly services that emphasize confidentiality and include flexible hours, integrated care, and reduced visit frequency [52,53], as well as decentralization of services such as through community adherence groups [1,8,51,54].…”
Section: Plos Medicinementioning
confidence: 99%
“…Furthermore, by drawing inferences from individuals’ stated choices, DCEs produce estimates of respondent preferences that are less subject to biases introduced when individuals are asked to explicitly report and assess the motivations underlying their choices [ 15 ]. Within the health services literature, DCEs have been used to elucidate patient preferences ranging from human papillomavirus vaccination among adolescent females [ 16 ] ,to treatment of osteoarthritis among older adults [ 17 ], and linkage to HIV care services among the general population [ 18 ]. However, few DCEs have examined HIV testing preferences in low or middle income countries (LMIC) [ 19 23 ] or among MSM.…”
Section: Introductionmentioning
confidence: 99%